Cecília Meireles e a Índia: das provisórias arquiteturas ao êxtase longo de ilusão nenhuma - Oliveira, Gisele Pereira de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The presence of India in Cecília Meireles’s biography is considerable. The relationship between the poetess and India presents itself both explicitly and implicitly in her writings: on one hand, there is the title Poems written in India, parallel to it there are a lot of chronicles and lectures about this country; on the other hand, dozens of poems allow the inference of premises, nuances, and themes related to Indian philosophical and religious thought, related to Hinduism and/or Buddhism. In this present analysis, we started up based on the premise that it is unavoidable both considering the poems on India (Indian sceneries, daily life and individuals), and the inventory of philosophical/religious aspects in the poems, by means of interpretative analysis, showing that India and Indian thought appear in Cecília’s poetry vertically and horizontally. In this light, we dedicate the first analytical sections to the country as a place at which Cecília devotes her attention, employ as background for several poems, and from where she elects some individuals about whom she writes. We approach, firstly, the relationship between Cecília and India, by looking at biographical data, travel chronicles and the analysis of the poem Hymn for peaceful India. Then, we discuss the relationship between Cecília and two renowned Indian personalities, in whose honor she dedicated poems, lectures, etc., i.e., the Indian poet, thinker and educator Rabindranath Tagore, and the poem The most divine poet, and the pacifist Mohandas K. Gandhi, and the poem Mahatma Gandhi. After that, we focus on the book Poems written in India, result of her trip there in 1953, and we consider, on one hand, Cecília as a traveler, and, on the other, her view on Indian women and their work as we analyze two poems, Humility and Puri Women. The latter in comparison to another poem, Ballad for the ten...

A presença da Índia na biografia e na obra de Cecília Meireles é notável. A relação entre a poetisa e a Índia apresenta-se de forma explícita e implícita em sua produção: por um lado, tem-se o volume Poemas escritos na Índia, paralelamente às diversas crônicas sobre esse país, assim como conferências e aulas; por outro lado, em sua lírica, há inúmeros poemas que permitem a leitura de princípios, temas e nuances do pensamento filosóficoreligioso tipicamente indiano, reconhecíveis como associáveis ao hinduísmo ou ao budismo. Em nossa análise, partimos da premissa de ser imprescindível tanto a leitura de poemas sobre a Índia (paisagens, cotidiano e personalidades), como o levantamento temático dos aspectos filosófico-religiosos indianos na lírica ceciliana, por meio de análises interpretativas de poemas, demonstrando que a Índia e o pensamento indiano se apresentam nessa poesia horizontal e verticalmente. Assim, as primeiras seções analíticas são dedicadas ao país como locus para o qual a poetisa volta sua atenção e o adota como cenário, como motivo de alguns poemas; ou do qual elege personagens sobre os quais trata. Abordamos, primeiramente, a relação entre a poetisa e a Índia, por meio de dados biográficos, crônicas e da análise do poema Cântico à Índia pacífica. Em seguida, falamos da relação de Cecília com os dois indianos renomados e analisamos poemas dedicados a eles: o pensador, educador e poeta Rabindranath Tagore e o poema Diviníssimo Poeta, e o pacifista Mohandas K. Gandhi, e o poema Mahatma Gandhi. Então, enfocamos o livro Poemas escritos na Índia, fruto de sua viagem à Índia em 1953, e pensamos, por um lado, em Cecília como poetisa-viajante, e discorremos brevemente sobre o ato de viajar para ela. E, por outro lado, averiguamos que a mulher indiana se destaca no volume, e, assim, analisamos dois poemas sobre a mulher...
Keywords: Meireles, Cecilia 1901-1964; Poesia; Filosofia oriental; Poetry - Authorship; India; Oriente